New particle formation dynamics in the central Andes: contrasting urban and mountaintop environments - D. Aliaga; V. A. Sinclair; R. Krejci; R. Krejci; M. Andrade; M. Andrade; P. Artaxo; L. Blacutt; R. Cai; R. Cai; S. Carbone; Y. Gramlich; et al. (Aerosol Research)
In this study, we investigate atmospheric new particle formation (NPF) across 65 d in the Bolivian central Andes at two locations: the mountaintop Chacaltaya station (CHC, 5.2 km above sea level) and an urban site in El Alto–La Paz (EAC), 19 km apart and at 1.1 km lower altitude. We classified the days into four categories based on the intensity of NPF, determined by the daily maximum concentration of 4–7 nm particles: (1) high at both sites, (2) medium at both, (3) high at EAC but low at CHC, and (4) low at both. These categories were then named after their emergent and most prominent characteristics: (1) Intense-NPF, (2) Polluted, (3) Volcanic, and (4) Cloudy. This classification was premised on the assumption that similar NPF intensities imply similar atmospheric processes. Our findings show significant differences across the categories in terms of particle size and volume, sulfuric acid concentration, aerosol compositions, pollution levels, meteorological conditions, and air mass origins. Specifically, intense NPF events (1) increased Aitken mode particle concentrations (14–100 nm) significantly on 28 % of the days when air masses passed over the Altiplano. At CHC, larger Aitken mode particle concentrations (40–100 nm) increased from 1.1 × 103 cm−3 (background) to 6.2 × 103 cm−3, and this is very likely linked to the ongoing NPF process. High pollution levels from urban emissions on 24 % of the days (2) were found to interrupt particle growth at CHC and diminish nucleation at EAC. Meanwhile, on 14 % of the days, high concentrations of sulfate and large particle volumes (3) were observed, correlating with significant influences from air masses originating from the actively degassing Sabancaya volcano and a depletion of positive 2–4 nm ions at CHC but not at EAC. During these days, reduced NPF intensity was observed at CHC but not at EAC. Lastly, on 34 % of the days, overcast conditions (4) were associated with low formation rates and air masses originating from the lowlands east of the stations. In all cases, event initiation (∼ 09:00 LT) generally occurred about half an hour earlier at CHC than at EAC and was likely modulated by the daily solar cycle. CHC at dawn is in an air mass representative of the regional residual layer with minimal local surface influence due to the barren landscape. As the day progresses, upslope winds bring in air masses affected by surface emissions from lower altitudes, which may include anthropogenic or biogenic sources. This influence likely develops gradually, eventually creating the right conditions for an NPF event to start. At EAC, the start of NPF was linked to the rapid growth of the boundary layer, which favored the entrainment of air masses from above. The study highlights the role of NPF in modifying atmospheric particles and underscores the varying impacts of urban versus mountain top environments on particle formation processes in the Andean region.